1997
DOI: 10.1046/j.1525-1497.1997.07128.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia in the elderly

Abstract: Geriatric patients should be considered at risk of developing hyperkalemia, especially when they are prescribed certain medications. Potassium levels should be monitored at appropriate intervals when these patients are treated with potassium-altering medications. Appropriate management of hyperkalemia in the elderly can avoid life-threatening neuromuscular and cardiac complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 90 publications
(215 reference statements)
0
35
1
Order By: Relevance
“…5,6 High pre-dialysis serum potassium (SK) is recognized as a risk factor for sudden death and all-cause mortality in HD patients. 7,8 Potassium has the potential to move freely across the dialyzer membrane during the HD session, typically being transferred from a patient’s blood into the dialysate.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 High pre-dialysis serum potassium (SK) is recognized as a risk factor for sudden death and all-cause mortality in HD patients. 7,8 Potassium has the potential to move freely across the dialyzer membrane during the HD session, typically being transferred from a patient’s blood into the dialysate.…”
Section: Introductionmentioning
confidence: 99%
“…This homeostasis plays a critical role in maintaining cellular resting membrane potential and neuromuscular function and is essential for normal activity of muscles, nerves, and the heart [3]. Hyperkalemia, resulting from an imbalance in K + homeostasis, is defined as a serum K + level of greater than 5.0 mEq/L and is further classified as mild, moderate, or severe [4,5]. It has been reported that drug therapy and impaired renal function are the main factors predisposing to the development of hyperkalemia [6-8].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperkalemia is a serious and potentially life-threatening electrolyte disorder that follows from a number of underlying abnormalities in potassium homeostasis [2]. It is recognized by the elevation of serum potassium above its upper normal level.…”
Section: Introductionmentioning
confidence: 99%